2023
DOI: 10.1021/acs.jmedchem.2c02036
|View full text |Cite
|
Sign up to set email alerts
|

Novel Indole–Chalcone Derivative-Ligated Platinum(IV) Prodrugs Attenuate Cisplatin Resistance in Lung Cancer through ROS/ER Stress and Mitochondrial Dysfunction

Abstract: Developing multifunctional platinum(IV) prodrugs via integrating bioactive pharmacophores into one entity is an attractive strategy to ameliorate the defects of platinum(II) drugs. Herein, a series of indole–chalcone derivative-ligated platinum(IV) complexes were synthesized and evaluated for their anticancer activities. Among them, optimal complex 17a exerted superior activity compared to that of cisplatin (CDDP) against the tested cells but showed lower cytotoxicity toward human normal lung cells. Detailed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…7,19 Therefore, to further investigate whether 16a could initiate mitochondrial apoptotic signaling pathway, we first study the effect of 16a on the changes of intracellular ROS generation via 2′,7′dichlorofluorescein diacetate (DCFH-DA) staining assays, using 14a, CDDP (5 μM), and combined group (14a + CDDP, 5 μM + 5 μM) as references. In line with our and others' reports, 7,19,32 CDDP was not able to increase the production of ROS in PANC-1/CDDP cells as compared with untreated group (Figure 5A,B). Besides, ROS levels in 14atreated group were 4.76-fold higher than those of the CDDPtreated group and were further elevated to 13.06-fold in the combined group, indicating that 14a and CDDP in combination were more potent to promote the ROS production.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…7,19 Therefore, to further investigate whether 16a could initiate mitochondrial apoptotic signaling pathway, we first study the effect of 16a on the changes of intracellular ROS generation via 2′,7′dichlorofluorescein diacetate (DCFH-DA) staining assays, using 14a, CDDP (5 μM), and combined group (14a + CDDP, 5 μM + 5 μM) as references. In line with our and others' reports, 7,19,32 CDDP was not able to increase the production of ROS in PANC-1/CDDP cells as compared with untreated group (Figure 5A,B). Besides, ROS levels in 14atreated group were 4.76-fold higher than those of the CDDPtreated group and were further elevated to 13.06-fold in the combined group, indicating that 14a and CDDP in combination were more potent to promote the ROS production.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The traces in Figure S4C,D revealed that 16a kept intact at 0 h treatment with AsA but was gradually reduced to another peak which appeared at the position of 14a along with the time process. In accordance with our and others’ reports, CDDP was not detected via HPLC. , However, the signals of CDDP ( m / z 299.0250) and hydrolyzed CDDP ( m / z 264.1563) were recorded via HR-MS (Figure S4H). Considering the acid condition of the tumor microenvironment, physiological condition, and biological medium, the stability of 16a in PBS (pH = 5.5 or 7.4) or DMEM (containing 10% fetal bovine serum) was measured.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On one hand, it has been one of the most promising strategies for designing a novel next-generation anticancer metal agent by rational screening the metal ion and ligand to synthesize metal complexes; on the other hand, the lipophilicity and anticancer activity of thiosemicarbazone compounds can be improved by modifying the hydrogen atom(s) at their N4 position with another group(s). , To obtain a new next-generation anticancer metal drug with high efficiency and low toxicity, we designed and synthesized a series of 2-hydroxy-1-naphthaldehyde thiosemicarbazone compounds by modifying the N3 position with an alkyl group or a phenyl group and then synthesized and characterized the corresponding Ru­(III) complexes. The crystal structures of Ru­(III) 2-hydroxy-1-naphthaldehyde thiosemicarbazone complexes ( 1b–4b ) were determined by X-ray crystallography (Figure ).…”
Section: Resultsmentioning
confidence: 99%